Pengaruh Art and Craft Activity terhadap Kualitas Hidup Lansia di Desa Donohudan, Kec. Ngemplak, Boyolali - Luqyana, Bilqis Salsabilla; Sri Wahyuni, Endang (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: In general, a person entering the elderly will experience limitations, so that the quality of life of the elderly decreases. Art and craft activity is used to make the elderly's life more meaningful by doing relaxation activities in their spare time so that it can have an impact on their quality of life. Objectives: To determine the effect of art and craft activity on the quality of life of the elderly in Donohudan Village, Ngemplak District, Boyolali. Methods: This research is a quantitative study using a pre-experimental design with one group pre test-post test. The sampling technique used was purposive sampling with a total sample of 23 samples. The instrument used was the World Health Organization Quality of Life (WHOQOL-BREF). The art and craft activity intervention was carried out 8 times. Data analysis used in the form of Paired Sample T-Test for physical and psychological domains, and Wilcoxon Signed Rank test for social relationship and environment domains. Results: The research sample was dominated by elderly female gender (95,7%), elderly age in the range of 60-75 years (82,6%), education level not in school (56,6%), and marital status does not have a partner (65,2%). The paired sample t-test hypothesis test on the physical and psychological domains and the Wilcoxon hypothesis test on the social relationship and environment domains showed that the p-value <0.05. Conclusion: There is an effect of art and craft activity on the quality of life of the elderly in Donohudan Village, Ngemplak District, Boyolali. Keywords : Quality of life, Elderly, Art and craft